Regulation of Kv4.3 voltage-dependent gating kinetics by KChIP2 isoforms - Patel, Sangita P (Blackwell Science Inc, 2004)
We conducted a kinetic analysis of the voltage dependence of macroscopic inactivation (τ(fast), τ(slow)), closed-state inactivation (τ(closed,inact)), recovery (τ(rec)), activation (τ(act)), and deactivation (τ(deact)) of Kv4.3 channels expressed alone in Xenopus oocytes and in the presence of the calcium-binding ancillary subunits KChIP2b and KChIP2d. We demonstrate that for all expression conditions, τ(rec), τ(closed,inact) and τ(fast) are components of closed-state inactivation transitions. The values of τ(closed,inact) and τ(fast) monotonically merge from −30 to −20 mV while the values of τ(closed,inact) and τ(rec) approach each other from −60 to −50 mV. These data generate classic bell-shaped time-constant–potential curves. With the KChIPs, these curves are distinct from that of Kv4.3 expressed alone due to acceleration of τ(rec) and slowing of τ(closed,inact) and τ(fast). Only at depolarized potentials where channels open is τ(slow) detectable suggesting that it represents an open-state inactivation mechanism. With increasing depolarization, KChIPs favour this open-state inactivation mechanism, supported by the observation of larger transient reopening currents upon membrane hyperpolarization compared to Kv4.3 expressed alone. We propose a Kv4.3 gating model wherein KChIP2 isoforms accelerate recovery, slow closed-state inactivation, and promote open-state inactivation. This model supports the observations that with KChIPs, closed-state inactivation transitions are [Ca(2+)](i)-independent, while open-state inactivation is [Ca(2+)](i)-dependent. The selective KChIP- and Ca(2+)-dependent modulation of Kv4.3 inactivation mechanisms predicted by this model provides a basis for dynamic modulation of the native cardiac transient outward current by intracellular Ca(2+) fluxes during the action potential.